Myotube-derived exosomal miRNAs downregulate Sirtuin1 in myoblasts during muscle cell differentiation - Forterre, Alexis (Landes Bioscience, 2014)
It has recently been established that exosomes can mediate intercellular cross-talk under normal and pathological conditions through the transfer of specific miRNAs. As muscle cells secrete exosomes, we addressed the question of whether skeletal muscle (SkM) exosomes contained specific miRNAs, and whether they could act as “endocrine signals” during myogenesis. We compared the miRNA repertoires found in exosomes released from C2C12 myoblasts and myotubes and found that 171 and 182 miRNAs were exported into exosomes from myoblasts and myotubes, respectively. Interestingly, some miRNAs were expressed at higher levels in exosomes than in their donor cells and vice versa, indicating a selectivity in the incorporation of miRNAs into exosomes. Moreover miRNAs from C2C12 exosomes were regulated during myogenesis. The predicted target genes of regulated exosomal miRNAs are mainly involved in the control of important signaling pathways for muscle cell differentiation (e.g., Wnt signaling pathway). We demonstrated that exosomes from myotubes can transfer small RNAs (C. elegans miRNAs and siRNA) into myoblasts. Moreover, we present evidence that exosome miRNAs secreted by myotubes are functionally able to silence Sirt1 in myoblasts. As Sirt1 regulates muscle gene expression and differentiation, our results show that myotube–exosome miRNAs could contribute to the commitment of myoblasts in the process of differentiation. Until now, myokines in muscle cell secretome provided a conceptual basis for communication between muscles. Here, we show that miRNA exosomal transfer would be a powerful means by which gene expression is orchestrated to regulate SkM metabolic homeostasis.